Metode Pendidikan Dalam Al-Qur’an (Studi Tafsir Ayat-Ayat Tarbawi) - Agus Pujiartha, Lalu; Sistiawan, Firman; Wahyudi; Aulia Nursalma, Nabila; Pitriyani (Bayani, 2023)
A method is a series of steps or techniques used by educators in the learning process so that students can achieve certain learning goals and skills. There are many verses in the Al-Qur'an that describe the use of methods in an educational context, such as in Surah Al-Maidah verse 67, An Nahl Verse 125, and Al-A'raf Verses 176-177. Based on these verses, it can be explained that the educational methods in the Qur'an include the Tabligh, Amtsal, Qudwah, Hikmah, Ibrah, and Mau'idzah methods. This research is a type of qualitative research, where researchers try to understand and interpret human behavioral interaction events in certain situations from their own point of view. To obtain data for this research, we used content or library analysis methods.